Vibration control of structure by optimising the placement of semi-active dampers and fuzzy logic controllers. Issue 3 (3rd July 2021) - Takin, Kambiz; Doroudi, Roozbeh; Doroudi, Siyamak
ABSTRACT: This study concentrates on applying semi-active dampers to control structures. In this paper, fuzzy algorithm types 1 and 2 have been used as controllers to evaluate the voltage of semi-active dampers. To design a proper fuzzy logic controller, membership functions and suitable rule sets need to be tuned and extracted. The location of a semi-active damper is very significant to reduce the responses of structure. In this paper, a 15-story building's responses for both uncontrolled and controlled (with MR dampers) situations subject to different ground motions are evaluated. Type 1 and type 2 fuzzy logic controllers, and the location of three MR dampers are optimised by Grey Wolf Optimiser, and also dissipating energies are investigated. The results show that although both optimised controllers can successfully reduce the seismic response of the building, the performance of the fuzzy type 2 controller is slightly superior than type 1. It is confirmed that the best location for dampers would be in the upper stories.